Synthesis and thiol‐responsive degradation of polylactide‐based block copolymers having disulfide junctions using ATRP and ROP. Issue 14 (29th August 2012) - Ko, Na Re; Yao, Kejian; Tang, Chuanbing; Oh, Jung Kwon
<x xml:space="preserve">Abstract</x> A new method to synthesize a variety of well‐controlled polylactide (PLA)‐based block copolymers having disulfide linkages at block junctions (PLA‐ss‐PATRPs) was investigated. The method uses a combination of ring‐opening polymerization (ROP) and atom transfer radical polymerization (ATRP) that initiates the synthesis of a new disulfide‐labeled double‐head initiator having both terminal OH and Br groups (HO‐ss‐iBuBr). The amount of tin catalyst and polymerization time significantly influenced the control of ROP initiated with HO‐ss‐iBuBr. A series of ATRP of various methacrylates as well as acrylate and styrene in the presence of the resulting PLA‐ss‐iBuBr macroinitiators proceeded in a living manner. These well‐controlled PLA‐ss‐PATRPs were further characterized for thermal properties using differential scanning calorimetry and thiol‐responsive degradation upon the cleavage of disulfide linkages. © 2012 Wiley Periodicals, Inc. J Polym Sci Part A: Polym. Chem. 2013, 51, 3071–3080